Sistem Pakar Untuk Mendiagnosa Penyakit Degeneratif Pada Lanjut Usia Menggunakan Metode Certainty Factor Berbasis Web - Dwi Saputra , Agung; Asnawi, Choerun; Bayu Saputra, Andika; Alfi Sa'diya, Nafisa (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Elderly is a natural process that undergoes organ changes that ultimately affect the state of the function and ability of the body as a whole. Degenerative diseases that occur in the elderly accompany the aging process in a person. This study aims to diagnose degenerative diseases in the elderly with an expert system.The Expert System which was built to diagnose degenerative in the elderly using the CF method aims to trace the symptoms displayed in the form of questions in order to diagnose diseases with web-based software.Expert system software can recognize degenerative diseases in the elderly experienced by users after answering some of the questions displayed by the application.The expert system designed can diagnose degenerative causes in the elderly because in this expert system knowledge is given in the form of symptoms that are used as input to the user.